2010
DOI: 10.1021/jp103823c
|View full text |Cite
|
Sign up to set email alerts
|

A New High-Pressure Polar Phase of Crystalline Bromoform: A First-Principles Study

Abstract: The high-pressure phases of bromoform at zero temperature have been investigated by first-principles pseudopotential plane-wave calculations based on the density functional theory. A new high-pressure polar phase, ε, with space group CC has been found after a series of simulated annealing and geometry optimizations. Our calculated enthalpies showed that the transition from β phase to γ phase occurs at 1 GPa, then the γ phase transforms to the ε phase at 90 GPa. In addition, the Br···Br and C-H···Br interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
4
5
0
Order By: Relevance
“…However, the enthalpy calculation (see Section 3.3) indicates that reidite is likely to occur as a thermodynamically metastable phase at pressures <7.3 GPa, where zircon is the most stable phase. The wolframite type phase also satisfies the Born criterion for monoclinic systems [43]. At pressures >75.8 GPa, wolframite is the stable polymorph, but reidite would occur as a metastable phase.…”
Section: Elasticity and Anisotropymentioning
confidence: 75%
“…However, the enthalpy calculation (see Section 3.3) indicates that reidite is likely to occur as a thermodynamically metastable phase at pressures <7.3 GPa, where zircon is the most stable phase. The wolframite type phase also satisfies the Born criterion for monoclinic systems [43]. At pressures >75.8 GPa, wolframite is the stable polymorph, but reidite would occur as a metastable phase.…”
Section: Elasticity and Anisotropymentioning
confidence: 75%
“…Moreover, it is observed that nonpolar symmetry to polar symmetry transformation took place in the bromoform and chloroform. 26,27 Therefore, the polar structure is perhaps favorable for crystalline haloform under high pressure. The calculated lattice parameters at 50 GPa for β-CHI 3 are a = 9.1303 Å, b = 5.5213 Å, c = 10.8126 Å, and β = 147.54 • .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the calculated metallization pressure of 32 GPa for CHI 3 is lower than that of 130 GPa for crystalline CHBr 3 in our early work. 27 The metallization pressure shows an attractive decrease with increment of halogen radius. This trend is well correlated with both the electronegativity of halogen and bandgap of halogen at ambient pressure.…”
Section: Birch-murnaghan Equation Of Statementioning
confidence: 99%
See 1 more Smart Citation
“…The only exception is iodoform (CH 3 I) which was studied by powder X-ray diffraction up to 40 GPa, and by Raman spectroscopy up to 22 GPa [27]. Computational studies on the high-pressure transformations of crystals containing tri-and dihalomethane are also scarce, with only CHBr 3 and CHI 3 investigated [38,39]. Table 1.…”
Section: Introductionmentioning
confidence: 99%